Semi-quantitative detection of Ureaplasma urealyticum biofilm in vitro and its correlation with macrolide resistance - Fei-yan LIN; Chun LU; Guo-xing ZHU; Pei-ying FENG; Han MA; Rong-biao LU; Song-chao YING (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2019)
Objective: To compare the ability of biofilm formation in 55 strains of Ureaplasma urealyticum (Uu) and their correlation with Uu resistance to macrolides. Methods: After in vitro biofilm cultures, optical density (OD) values of extracellular matrix of biofilm of Uu 55 strains were measured semi-quantitatively. The drug sensitivity tests (erythromycin, azithromycin, josamycin and clindamycin) were performed before and after biofilm formation. Paired t-test was used to determine the significances between the minimum inhibitory concentration (MIC) for Uu and the minimum biofilm inhibitory concentration (MBIC) for Uu biofilm. The relationship between OD value and log2 (MBIC/MIC) value was analyzed with simple linear regression. Results: For 55 Uu strains, MBICs were higher than MIC for all four antibiotics (all P<0.001). MBICs of four antibiotics for 55 Uu strains arranged in descending order were erythromycin, clindamycin, azithromycin, and josamycin. In contrast, log2 (MBIC/MIC) values listed in descending order were josamycin, azithromycin, clindamycin and erythromycin. Simple linear regression analysis showed that the OD value of Uu biofilm correlated positively with log2 (MBIC/MIC) values of azithromycin, josamycin and clindamycin. Conclusions: The ability of Uu to form biofilm correlates positively with the resistance of Uu biofilm to azithromycin, josamycin and clindamycin.